Arkhivy Kremlia - izdanie podgotovili N. N. Pokrovskii, S. G. Petrov. (Sibirskii khronograf ; Rossiiskaia politicheskaia entsiklopediia)
Partial contents: Vol. 1. Politbiuro i tserkov´, 1922-1925. - Vol. 2. Politiuro i tserkov´, 1922-1925.